Studi Kasus Pria 33 Tahun dengan Abses Serebri - Chaira Khuntum Roskaulya; Yofinda Aurelia Rizkita (STIKes Ibnu Sina Ajibarang, 2024)
A cerebral abscess is an infection of brain tissue enveloped by a capsule and localized to one or more areas within the brain. The source of infection of a cerebral abscess is usually from an infection of another body part that spreads through the tissue directly or through blood vessels. About 75% of cerebral abscesses originate from the spread of otitis, mastoiditis, frontal sinusitis or skull fracture. Most brain abscesses originate from direct spread of infection in the middle ear, sinusitis, or mastoiditis. Sinusitis can be paranasal sinusitis, ethmoidal, sphenoidal and maxillary sinusitis. Diagnosis requires a computed tomography scan (CT-Scan). Laboratory examination is also necessary to determine the cause of the patient's clinical symptoms. Appropriate use of antibiotics is aimed at keeping the patient alive in the hope that the cerebral abscess will improve. Conservative measures, and control of ICP increase. The method used is using a case study. This case study discusses Mr. Mr. O 33 years old with a cerebral abscess with a precipitating factor of unresolved dental infection by conducting a history, physical examination, and supporting and performing management and education that may be applied to patients in the future.